Waste Bombyx Mori Silk Textiles as Efficient and Reuseable Bio-Adsorbents for Methylene Blue Dye Removal and Oil–Water Separation - Hansadi Jayamaha; Isabel Schorn; Larissa M. Shepherd (Fibers)
Many adsorbent materials are being studied for dye and oil removal from the environment. Bio-based materials such as silk are promising candidates due to their enhanced affinity for dyes and intrinsic hydrophobicity. This work extensively studies various silk textiles as dye and oil adsorbents. For comparison, we use electrospun fiber mats and hollow silk microparticle-treated silk fabrics. Our work is motivated by two factors: (i) massive amounts of silk waste is being discarded annually from textile factories, and (ii) the limited studies on the adsorption phenomena of pristine silk textiles. Based on our findings, 12 mg of silk filament yarn has a 90% methylene blue (MB) removal efficiency within 10 min of exposure for concentrations up to 100 ppm and exhibits adsorption capacities of 145 mg/g for 800 ppm concentrations. The adsorption kinetics obey a pseudo-second order, where the rate-controlling step is chemisorption, and isotherms follow the Langmuir model with homogenous monolayer adsorption. Furthermore, noil woven fabrics with contact angles of 1400 have oil adsorbent capacities that are double the fabric weight. Our work confirms that silk waste textiles are efficient and reusable bio-adsorbents for MB dye and oil removal, outperforming materials made with additional and energy-intensive techniques such as silk dissolution and electrospinning.